Pembuatan Dokumen Hazard Identification, Risk Assessment, Risk Control (HIRARC) di PT Evercoss Technology Indonesia - Yulius Pambudi Cahyo Nugroho Sandjaja; Kriswanto Widiawan (Jurnal Titra, 2022)
PT. Evercoss Technology Indonesia, is a technology-based company that requires valid data to carry out safe and comfortable business activities. Based on the results of interviews with the company that there have been several work accidents while the company is in the new industrial area. By designing documents using HIRARC, it is hoped that it will help PT Evercoss Technology Indonesia in identifying various potentially hazardous work activities, by conducting a risk assessment of potentially hazardous work activities, to providing suggestions for risk control of potential hazards. The results obtained from making the HIRARC document show that there are several work activities that have the potential to be hazardous, namely 12 work activities that have very low potential hazards, 23 work activities that have low potential, 21 work activities that have moderate potential hazards and 2 work activities that have potential hazards. tall. The last stage is to control risk in several ways, namely elimination, substitution, engineering/technical design, administration, and Personal Protective Equipment (PPE). The proposed risk control is expected to reduce the level of risk that occurs at PT Evercoss Technology Indonesia.